(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A bank is a financial institution that creates credit by lending money to a borrower, thereby creating a corresponding deposit on the bank’s balance sheet. Lending activities can be performed either directly or indirectly through capital markets. Due to their importance in the financial system and influence on national economies, banks are highly regulated in most countries. Most nations have institutionalized a system known as fractional reserve banking under which banks hold liquid assets equal to only a portion of their current liabilities. In addition to other regulations intended to ensure liquidity, banks are generally subject to minimum capital requirements based on an international set of capital standards, known as the Basel Accords. Banking system occupies an important role in the economy of a nation. In fact, banking system of any country is the lifeblood of an economy.